DETERMINATION OF CAREER PLANNING AND DECISION MAKING: ANALYSIS OF COMMUNICATION SKILLS, MOTIVATION AND EXPERIENCE (LITERATURE REVIEW HUMAN RESOURCE MANAGEMENT) - Fahmi, Idham; Hapzi Ali (Dinasti International Journal of Management Science, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the Determination of Career Planning and Decision Making: Analysis of Communication Skills, Motivation and Experience, A Study of the Marketing Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are that: 1) The Effect of Communication Skills on Career Planning; 2) The Effect of Motivation on Career Planning; 3) Effect of Experience on Career Planning; 4) The Effect of Career Planning on Decision Making; 5) The Influence of Communication Skills on Decision Making; 6) The Influence of Motivation on Decision Making; and 7) Effect of Experience on Decision Making.